Development of Smart Electrochromic Film Device - Anas Akasyah Abd Patas,; Nur Athirah Mohd Taib,; Syahida Suhaimi, (Multidisciplinary Applied Research and Innovation, 2023)
The demands for smart devices are increasing exponentially nowadays. This project presents the invention of a new, low-cost, and user-controlled electrochromic film device for home safety and privacy purpose. The development of this system focuses on windows where electrochromism materials as a film had been layered for the safety and privacy plan. Excessive exposure to UV radiation over 15 minutes causes acute and chronic long-term skin effects. Meanwhile, the high cost of cutting precise glass appliances due to the high volume of heat trapped during daylight causes the application of this device to be crucial. This invention is equipped with IoT (Internet of Things) which helps users to control it remotely via Blynk Apps in smartphones and displays all the sensor’s output. The system comprised of Arduino UNO as the main controller, NodeMCU ESP8266 for IoT platform, solar battery as a power source, UV sensor together with PIR sensor to enhance safety purpose and DHT11 for monitoring temperature and humidity.